2012
DOI: 10.1002/mar.20431
|View full text |Cite
|
Sign up to set email alerts
|

When Satisfied Consumers Do Not Return: Variety Seeking's Effect on Short‐ and Long‐Term Intentions

Abstract: Even satisfied consumers frequently do not come back, which challenges loyalty theory and marketing practice. It is reasoned that variety-seeking tendencies will significantly affect short-term revisit intentions, whereas satisfaction and regret will mostly determine long-term revisit intentions. Thus, the influence of satisfaction on loyalty is hypothesized to be critically dependent on the time perspective of the intentions, now or later, and variety seeking. A representative survey (N ‫؍‬ 400) in eight Span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 66 publications
(81 reference statements)
6
53
0
3
Order By: Relevance
“…Prior literature has also suggested that commitment, switching experiences, and variety seeking are central drivers of customers' intention and behavior (Garbarino and Johnson 1999;Homburg et al 2007;Sheth and Parvatiyar 1995;Sánchez-García et al 2012). We assert that affective commitment, switching experiences, and variety seeking are reflections of consumers' assessments and perceptions of an emotional or a social value that they derive from relationships.…”
Section: Emotional and Social Value Perceptionsmentioning
confidence: 78%
See 1 more Smart Citation
“…Prior literature has also suggested that commitment, switching experiences, and variety seeking are central drivers of customers' intention and behavior (Garbarino and Johnson 1999;Homburg et al 2007;Sheth and Parvatiyar 1995;Sánchez-García et al 2012). We assert that affective commitment, switching experiences, and variety seeking are reflections of consumers' assessments and perceptions of an emotional or a social value that they derive from relationships.…”
Section: Emotional and Social Value Perceptionsmentioning
confidence: 78%
“…For defected customers, their former supplier can become attractive again if it can demonstrate new or Bnovel^differentiated products or services. Accordingly, Sánchez-García et al (2012) find that variety seeking customers develop higher revisit intentions in the long run (in a non-contractual setting). Since customers who are prone to variety seeking search actively for new offers, a former supplier can again become relevant and thus customers are more willing to return.…”
Section: Emotional and Social Value Perceptionsmentioning
confidence: 95%
“…Specifically, prior studies have confirmed that satisfaction is favourably related to purchase intention (Lin and Lekhawipat 2014;Pee et al 2018;Wen et al 2011;Yen and Lu 2008). Hence, it has been proved that satisfied customers tend to repurchase more than dissatisfied consumers (Sánchez-García et al 2012). In addition, it has been proved in the online context that satisfaction positively and significantly influences behavioural e-loyalty regarding search engines (Sirdeshmukh et al 2018), about tourism e-commerce (Gonçalves et al 2016), among female online shoppers (Chou et al 2015), regarding luxury brands (Yoo and Park 2016), among others.…”
Section: Relational Variables In Local Food E-commercementioning
confidence: 86%
“…Conversely, low satisfaction or dissatisfaction is highly associated with negative emotions and unfavorable behavioral intentions regarding the particular consumption experience, such as negative word of mouth or switching behavior. However, recent research also indicated that even satisfied customers might not return in the short-term due to variety seeking tendencies (Sánchez-García et al, 2012). This suggests that customer satisfaction is a critical factor determining revisit intentions, but its effects could differ depending on short-term or long-term revisit intentions when variety seeking tendencies are considered.…”
Section: Customer Satisfaction and Variety Seekingmentioning
confidence: 96%